Clinical manifestations of rotavirus diarrhea in the outpatient clinic of Cipto Mangunkusumo Hospital, Jakarta - Teny Tjitrasari; Agus Firmansyah; Imral Chair (Indonesian Pediatric Society Publishing House, 2016)
Background Rotavirus is one of the most common cause of acute diarrhea among hospitalized and pediatric outpatients, especially those aged 6-24 months. Data of hospitalized children showed that rotavirus causes severe diarrhea, but data of outpatient children in Indonesia, especially at Cipto Mangunkusumo Hospital Jakarta, is limited. Objective To characterize the clinical manifestations of rotavirus diarrhea in the pediatric outpatient clinic at Cipto Mangunkusumo Hospital Jakarta. Methods This was a cross-sectional study, done in July 2003 - March 2004. Stool specimens were collected from patients aged 6-24 months with diarrhea and tested for rotavirus by ELISA. Result Of the 98 children enrolled, 35 (35.7%) children excreted rotavirus. Rotavirus diarrhea was seen in 43.8% of children aged 6-11 months, of whom 37.0% of them were undernourished. Males were affected 1.4 times as much as females. The clinical manifes- tations were passage of diarrheic stools more than 10 times a day (58.3%), mild-moderate dehydration (55.8%), cough (51.9%), rhinorhea (46.0%), vomiting (44.8%), fever (41.1%), yellow stools (38.9%), and mucus in the stool (20.0%). The highest prevalence of rotavirus diarrhea was identified in the combination of diarrhea, fever, vomiting and cough/rhinorrhea (55.3%). Stool analysis re- vealed that the prevalence of rotavirus diarrhea among children with fat malabsorption, lactose malabsorption, and stool leukocyte of +2 were 50.0%, 46.7% and 33.9%, respectively. Conclusion The prevalence of rotavirus diarrhea in the pediatric outpatient clinic of Cipto Mangunkusumo Hospital, Jakarta was 35.7%. The highest prevalence of rotavirus diarrhea was identified in the combination of diarrhea, fever, vomiting and cough/rhinorhea (55.3%)